Chronic Inflammatory Bowel Disease - Recent aspects Chronisch entzündliche Darmerkrankungen - Aktuelle Aspekte - Vieth, M.; Rath, Timo; Bästlein, E. C.; Neumann, Helmut (Endoskopie heute, 2015)
Inflammation plays a huge role in carcinogenesis in inflammatory bowel disease (IBD). Due to the close relation of extent and degree of inflammation in colitis-associated carcinomas modern treatment strategies seek for minimizing mucosal inflammation or even mucosal healing. Gastrointestinal endoscopy and histopathology play a pivotal role not only for diagnostics but also for endoscopic removal. Clear cut definitions of criteria are mandatory to ensure a high quality setup. At our institution more than 90% of all carcinomas in IBD develop in ulcerative colitis. Therefore, we will focus on ulcerative colitis and ulcerative colitis-associated carcinomas in the present manuscript. It is known that aside from specialized centers that instead of performing proctocolectomies partial colectomies are carried out in case of colitis-associated carcinomas. Our retrospective data show that partial colectomies bear a higher risk for relapses on base of lymph node metastases and metachronous lesions as well. Survival rates of partial and complete colectomies are comparable but proctocolectomies are still the therapy of choice for carcinomas in ulcerative colitis.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Crohn's disease; histology carcinoma; treatment; ulcerative colitis